Analisis Pengaruh Bentuk Slidding Roller Terhadap Torsi dan Daya Kendaraan Berbasis Continously Variable Transmission - Wijaya, Dedik Ananta; Dantes, Kadek Rihendra; Pasek Nugraha, I Nyoman (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to determine the ratio of power and torque on an automatic motorbike using two different rollers, namely a cylindrical roller with a sliding roller with a weight of 12 grams each. The method used in this research is the experimental method. The testing and retrieval process carried out at the Gede Widi Motor workshop, and data collection was carried out five repetitions for each variation. After testing, there are differences in torque and power on the cylinder roller with roller sliding. The cylinder roller reaches the highest torque of 7.6 Nm at Rpm 4000. The highest power is 7.46 Hp at Rpm 7000, while in roller sliding, the highest torque is 11.82 Nm at Rpm 4000 and the highest power 7.56 Hp at 7000 RPM.